2021
DOI: 10.3390/foods10010102
|View full text |Cite
|
Sign up to set email alerts
|

High Moisture Extrusion of Soy Protein: Investigations on the Formation of Anisotropic Product Structure

Abstract: The high moisture extrusion of plant proteins is well suited for the production of protein-rich products that imitate meat in their structure and texture. The desired anisotropic product structure of these meat analogues is achieved by extrusion at high moisture content (>40%) and elevated temperatures (>100 °C); a cooling die prevents expansion of the matrix and facilitates the formation of the anisotropic structure. Although there are many studies focusing on this process, the mechanisms behind the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 86 publications
(123 reference statements)
2
65
0
Order By: Relevance
“…Since micro-CT imaging is a non-invasive method for assessing three-dimensional network structures, it is expected that small differences in anisotropic structure can be visualized more precisely with this non-invasive method than with the invasive method of tearing the extrudates. It is known from the literature that, in high-moisture extrusion, the anisotropic product structure is formed by the multiphase protein matrix being deformed by shear stresses in the cooling die [11,24]. However, it is possible that in our case the added oil leads to wall slip regardless of the addition point and the rheological properties.…”
Section: Positionmentioning
confidence: 80%
See 2 more Smart Citations
“…Since micro-CT imaging is a non-invasive method for assessing three-dimensional network structures, it is expected that small differences in anisotropic structure can be visualized more precisely with this non-invasive method than with the invasive method of tearing the extrudates. It is known from the literature that, in high-moisture extrusion, the anisotropic product structure is formed by the multiphase protein matrix being deformed by shear stresses in the cooling die [11,24]. However, it is possible that in our case the added oil leads to wall slip regardless of the addition point and the rheological properties.…”
Section: Positionmentioning
confidence: 80%
“…A common process to create these is high-moisture extrusion with an attached cooling die. During the extrusion process, the plant proteins are mixed with water, heated, sheared, and forced through the cooling die, resulting in the formation of an anisotropic structure [4][5][6][7][8][9][10][11][12][13][14][15]. The consumer's expectations for the sensory properties of meat analogues are the same as the expectations for the typical sensory properties of meat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High moisture extrusion (HME) can be used to produce meat analogues from plant-based, protein-rich raw materials that are intended to mimic meat in terms of its unique structure, texture, and mouthfeel [ 1 , 2 ]. The studies on HME, which started in the 1980s [ 3 , 4 , 5 ], can basically be classified into two different categories, which refer to the use of the raw material, either single-component, where only a single protein-rich raw material (e.g., a protein concentrate or isolate) was used [ 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], or multi-component, where two or more raw materials were mixed together [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. For both categories, it was shown that anisotropic meat-like structures were created in the process.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we showed that a multiphase system is formed in the single-component extrudates based on soy protein isolate (SPI) in which the phases differ in their water concentration [ 10 ]. According to the model of Tolstoguzov [ 24 ], this multiphase system arises as a result of the thermodynamic incompatibility of the proteins involved.…”
Section: Introductionmentioning
confidence: 99%